Consequences of the Lack of CD73 and Prostatic Acid Phosphatase in the Lymphoid Organs - Yegutkin, Gennady G.; Auvinen, Kaisa; Karikoski, Marika; Rantakari, Pia; Gerke, Heidi; Elima, Kati; Maksimow, Mikael; Quintero, Ileana B.; Vihko, Pirkko; Salmi, Marko; Jalkanen, Sirpa (Mediators of Inflammation, 2014)
CD73, ecto-5′-nucleotidase, is the key enzyme catalyzing the conversion of extracellular AMP to adenosine that controls vascular permeability and immunosuppression. Also prostatic acid phosphatase (PAP) possesses ecto-5′-nucleotidase/AMPase activity and is present in leukocytes. However, its role related to immune system is unknown. Therefore, we analyzed enzymatic activities and leukocyte subtypes of CD73 and PAP knockouts and generated CD73/PAP double knockout mice to elucidate the contribution of CD73 and PAP to immunological parameters. Enzymatic assays confirmed the ability of recombinant human PAP to hydrolyze [3H]AMP, although at much lower rate than human CD73. Nevertheless, 5′-nucleotidase/AMPase activity in splenocytes and lymphocytes from PAP−/− mice tended to be lower than in wild-type controls, suggesting potential contribution of PAP, along with CD73, into lymphoid AMP metabolism ex vivo. Single knockouts had decreased number of CD4+/CD25+/FoxP3+ regulatory T cells in thymus and CD73/PAP double knockouts exhibited reduced percentages of CD4+ cells in spleen, regulatory T cells in lymph nodes and thymus, and CD4+ and CD8+ cells in blood. These findings suggest that PAP has a synergistic role together with CD73 in the immune system by contributing to the balance of leukocyte subpopulations and especially to the number of regulatory T cells in lymph nodes and thymus.